Changing Black Youth’s Futures: Stop Anti-Black Racism in Education in Quebec - Lewis, Lerona Dana; Cozier, Gloria Ann (Université d'Ottawa | University of Ottawa, 2025)
This report presents the experiences of Black youth in Quebec schools, including the impact of the COVID-19 pandemic, from the perspectives of parents, children, and teachers. There were fifty-three (53) eligible participants enrolled in the study. The majority of the participants, forty-one (41) or 77%, were Anglophone. Data were collected using individual interviews and a focus group. Our data analysis identified four central themes about current school practices that affect Black youth. These are (1) exclusionary academic practices, (2) unfair resource allocation and support practices, (3) marginalizing pedagogical practices, and (4) inadequate decision-making and accountability practices. None of the teachers we interviewed reported knowing about programs to support Black youth in their high schools or CEGEPs. However, they all reported that Black youth are adversely affected by stereotyping and teachers’ low expectations. The results of this research underscore that Black students’ academic trajectories must be addressed by education policymakers in Quebec. In this research, there was a notable absence of discussion about students’ religious experiences in school or their gender identity. Thus, the findings do not capture how school practices impact Black youth who live at the intersection of race, religion, and gender diversity in Quebec. Future research in this area is recommended.
Keywords: Black Youth; Montreal High School Students; Black Teachers; Black Parents; Classe d'accueil; Welcoming Class; Black Youth School Success; Greater Montreal Area Education; Anti-Black Racism; Anti-Blackness in Education; French Second Language Learning (FSL); Inequity in Education